First-principles molecular dynamics simulation study on Ti4+ ion in aqueous sulfuric acid - Choe, Yoong-Kee; Tsuchida, Eiji; Tokuda, Kazuya; Otsuka, Jun; Saito, Yoshihiro; Masuno, Atsunobu; Inoue, Hiroyuki (AIP advances, 2021)
A first-principles molecular dynamics simulation study was carried out to investigate the structural features of Ti4+ in aqueous sulfuric acid. Ti4+ forms several stoichiometric compounds in aqueous sulfuric acid, the identity and structural information details of which have been the subject of numerous studies. Three stoichiometric compounds of Ti4+ in aqueous sulfuric acid were found in the simulations, namely, [Ti=O(OH)2(H2O)3], [Ti(OH)2(H2O)2SO4], and [Ti2O2(H2O)5(OH)2SO4]. The results indicated that HSO4− formed a complex with the Ti ion by releasing its proton, which implies that such a coordination increases the proton concentration in the solution. The multinuclear complex was formed in our simulation conditions (concentration: 1M Ti4+ and temperature: 353 K); the result supports the interpretation of a previous experimental study.